THE INFLUENCE OF FINANCIAL PERFORMANCE ON STOCK RETURN IN RETAIL COMPANY - Santoso, Indrie Gusta; Meidiaswati, Harlina (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2022)
Introduction: Investors need to understand the company's financial performance and other factors to make the right investment decisions. This study aims to analyze the effect of profitability, liquidity, leverage, and firm size on stock returns. Methods: This research is a quantitative study. A sample of 16 companies was taken purposively from 28 retail companies for the 2016-2020 period. The analytical technique used is multiple linear regression Results: Profitability (return on assets), liquidity (quick ratio), and firm size have no significant effect on stock returns, while leverage (debt to equity ratio) has a significant positive effect on stock returns. Conclusion and suggestion: Further researchers can add other variables that are not included in this research model in order to find out the variables that can affect stock returns.